The MDR Upon Admission Score: Shortening Time to Initiation of Appropriate Antimicrobial Therapy in the Era of Resistance in the Community. (4th October 2017) - Zilberman-Itskovich, Shani; Lazarovitch, Tsilia; Zaidenstein, Ronit; Dadon, Mor; Daniel, Chen; Marchaim, Dror
Abstract: Background: Multi-drug-resistant organisms (MDRO) pose a growing burden, including in the community. Delay in initiation of appropriate antimicrobial therapy (DAAT) is common among patients with MDRO infection. In addition, DAAT is the strongest modifiable predictor of mortality in severe sepsis. The aim of this study was to develop a prediction score for MDRO infection upon admission to hospitals, in order to shorten DAAT and reduce misuse of broad-spectrum antibiotics administered to patients with non-MDRO infection. Methods: Retrospective case–control analysis was conducted at Assaf Harofeh Medical Center, Israel, for two consecutive months (08-10/2016). Adult patients with MDRO infections were compared with patients presenting with non-MDRO sepsis (i.e., patients with microbiologically confirmed non-MDRO infection, or patients with non-microbiologically confirmed diagnosis). MDROs were determined in accordance to established criteria. A prediction score was developed based on the multivariable analysis (logistic regression) of predictors for MDRO infection upon admission. Results: The primary dataset consisted of 677 patients, 78 had MDRO infection. The final score included nine parameters: home therapy (IV therapy, wound care, or specialized nursing care, 23 points), history of MDRO colonization (13 points), invasive procedure in the past 6 months (11 points), any antibiotics in the past 3 months (10 points), elderly (over 65 years, 8 points), severe sepsis (i.e., severe sepsis, septic shock, or multi-organ failure, 6 points), resident of long-term care facility (5 points), acute kidney injury (5 points), and congestive heart failure (3 points), . A cut-off of ≥22 points had a sensitivity of 83%, specificity of 76%, and ROC AUC = 0.86 (figure). Conclusion: This study presents a novel prediction score for MDRO infection upon admission, based on parameters that could easily be extracted at bedside during the initial presentation of a patient with sepsis. A future prospective interventional study is needed in order to quantify the performances of this score in terms of shortening DAAT, curbing misappropriate use of broad-spectrum antibiotics, and improving patients' outcomes. Disclosures: All authors: No reported disclosures.